Archeologie mlýnů zaniklých ve druhé polovině 20. století - Galusová, Lucie (Acta Universitatis Lodziensis. Folia Archaeologica, 2018)
Case studies of watermills that ceased to exist during the 20th century, examined via archaeological methods in the regions of West and Northwest Bohemia, have brought significant findings in the form of particular building stages from the oldest times to the turn of the 19th and 20th centuries. The Watermill of Hutmühle (Litoměřice district, Northwest Bohemia, near the village of Zubrice) was the most thoroughly investigated site. In the scope of this archaeological excavation, various methodological differences, possibilities and limits of research of such sites appeared. Based on the scientific activities performed, it is evident that these watermills are highly valuable technical sights, which shall be paid more attention to in terms of both archaeological and historical monument care.